Pengaruh Profitabilitas, Leverage, Dan Capital Intensity Terhadap Penghindaran Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Nisak Amalia; Yunus Harjito; Siddiq, Faiz Rahman (Pusat Riset dan Inovasi Nasional, 2026)
Tax avoidance refers to efforts by companies to reduce their tax obligations through methods that remain within the boundaries of applicable laws and regulations. Taxes are often perceived as a burden because they decrease a company’s profits, leading some companies to engage in actions aimed at minimizing tax payments. Such practices may be viewed as not meeting societal expectations, as tax revenues are managed by the government to provide benefits to the public in the form of social assistance and public services.This study examines companies in the consumer goods industry listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with a total of 200 observations used as the research sample. The study employs secondary data obtained from financial statements and annual reports available on company websites and the IDX. The analytical methods used consist of multiple linear regression analysis and Moderated Regression Analysis (MRA), processed using IBM SPSS software.The findings indicate that profitability has a significant negative effect on tax avoidance, implying that more profitable companies tend to engage less in tax avoidance practices. Leverage shows a significant positive effect, suggesting that companies with higher debt levels are more likely to avoid taxes. Meanwhile, capital intensity is found to have no significant effect on tax avoidance. Additionally, company size moderates the relationship between profitability and leverage on tax avoidance but does not moderate the relationship between capital intensity and tax avoidance.